Traveling Waves in the Underdamped Frenkel–Kontorova Model. (30th April 2018) - Li, Hengyan; Liu, Shaowei
Abstract : This paper studies a damped Frenkel–Kontorova model with periodic boundary condition. By using Nash–Moser iteration scheme, we prove that such model has a family of smooth traveling wave solutions.